Fluorescence Lifetime Imaging of Propranolol Uptake in Living Glial C6 Cells - Bisby, Roger; Botchway, Stanley; Crisostomo, Ana; Parker, Anthony; Scherer, Kathrin (Spectroscopy: An International Journal, 2012)
Uptake of the β-blocker drug propranolol by living glial C6 cells has been observed using fluorescence lifetime imaging with two-photon excitation at 630 nm. Both uptake and release of propranolol occur within minutes and are temperature dependent, being about 5 times faster at 37°C than at 20°C. The intracellular fluorescence lifetime of propranolol is generally shorter than the value of 9.8 ns determined in dilute neutral aqueous solution, and the difference is ascribed to concentration quenching. Within the cells, propranolol is accumulated within intracellular acidic vesicles and the cytoplasm but is excluded from the cell nucleus. On incubation of cells in medium containing 100 μM propranolol, the drug is accumulated to reach intracellular concentrations up to 10 mM in a process that is believed to be driven by protonation within acidic cellular compartments.